2018
DOI: 10.1111/nhs.12413
|View full text |Cite
|
Sign up to set email alerts
|

Association of health literacy with health information‐seeking preference in older people: A correlational, descriptive study

Abstract: Low health literacy has been recognized as a potential barrier to obtaining knowledge and maintaining self-care in older people. However, little is known about information-seeking preference in relation to health literacy among older people. The aim of the present study was to understand the influence of health literacy on the information-seeking preference of older people. A total of 129 community-residing Korean older people completed a survey in 2016. The findings revealed that health literacy was a signifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
30
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(33 citation statements)
references
References 24 publications
(40 reference statements)
3
30
0
Order By: Relevance
“…According to empirical evidence, limited FHL negatively affects an individual's motivation and capacity to seek, comprehend and act on health information. For example, Kim and Utz (2018) demonstrated that FHL operated as an independent indicator of preference for seeking health information among chronically ill patients. In addition, those with limited FHL accessed health information from fewer resources and were more likely to use television but not printed media or health organization documents as their main source of health information (Yoshida, Iwasa, Kumagai, Suzuki, & Yoshida, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…According to empirical evidence, limited FHL negatively affects an individual's motivation and capacity to seek, comprehend and act on health information. For example, Kim and Utz (2018) demonstrated that FHL operated as an independent indicator of preference for seeking health information among chronically ill patients. In addition, those with limited FHL accessed health information from fewer resources and were more likely to use television but not printed media or health organization documents as their main source of health information (Yoshida, Iwasa, Kumagai, Suzuki, & Yoshida, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, feasible alternatives for clinical practice should be considered,29 such as using single item questions,28 48 or prompt lists49 preferably tested by the target group to avoid comprehension problems,41 50 51 but, above all, by supporting patients to understand information. Besides asking patients directly about their understanding and the kind of information and/or (practical) support they might need, patients should be provided tools to ensure they understand, but can also recall what has been said 16 52. Two examples worth mentioning are the Ask Me 3 questions campaign53 or the use of the teach-back method 54.…”
Section: Discussionmentioning
confidence: 99%
“…From the point of view of older individuals, SDL has been documented as the most widely used method (Knowles, ; Roberson, ), low‐cost and available strategy for learning, without being affected by gender, race or class differences (Narushima, Liu, & Diestelkamp, ). From the nurses’ point of view, when educational interventions are needed, taking individuals’ needs and preferences into consideration has become imperative in all healthcare settings, especially among older people (Kim & Utz, ). However, despite its relevance, patient education has often been reported as a missed care component by nurses due to various factors (Iden, Ruths, & Hjørleifsson, ; Vryonides et al, ), such as the absence of tools for evaluating SDL abilities (Boulton‐Lewis, ; Roberson, ), which also slows the development of evidence in this field.…”
Section: Discussionmentioning
confidence: 99%
“…With the increasing age of the population and the need to promote active ageing (Coleen, ; LeBlanc & Jacelon, ), HL has become crucial also among older people and for all those who provide care to them (Coleen, ; León‐González et al, ; Wang et al, ). By evaluating HL among older people, nurses can provide a more effective education and improve health outcomes (Swider, Levin, & Reising, ) by developing effective self‐management abilities (Kim & Utz, ). In daily practice, this implies an active involvement of older individuals, the evaluation of their HL level, as well as their SDL abilities: these elements have been documented as prerequisites of tailored educational opportunities aimed at informing, providing evidence and stimulating their looking for clarifications from nurses themselves (Harbour & Greall, ; Kim & Utz, ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation